A escola inclusiva na perspectiva de estudantes com surdez público da educação de jovens e adultos - Alecrim, Sumara Barbosa (2021)
The fight for the right to education for the Target Public of Special Education (PAEE) has come a long way and this context encompasses Youth and Adult Education (EJA). Reflecting on the proposal of inclusive schools, social movements and the State's attempts to guarantee education for all, this research aimed to analyze the access, permanence, Specialized Educational Service (AEE) and the learning of deaf students in EJA. This is a research with a qualitative approach, at a descriptive level, with a case study design. Two deaf students enrolled in EJA, in a regular school in a city in the interior of São Paulo, participated. In data collection, semi-structured interviews and document review were used as instruments. For data analysis, the principles of the Collective Subject Discourse analysis were used, allowing the organization of the contents. We obtained the construction of five categories: accessibility, permanence, specialized educational service, learning and perspective, based on elements and characteristics in common between the sources. Data were analyzed and discussed in conjunction with the theoretical frameworks used. The results show that, considering the document search, the public policy on education is based on legislation in order to meet the needs of people and guarantee their rights, and also that, from the movement of society, this policy can create other laws, decrees, deliberations, regulations, guidelines for the benefit of all, or a majority, at the national and municipal levels. But considering what deaf students say about their educational experience, these laws still do not meet them, the school is not inclusive, access to communication, information, interaction, learning, assessment, specialized educational care, resources adapted materials and teaching materials are not possible. The conclusions, according to these sayings, trigger some inferences about the means or “channels” for disclosing information and rights and about the fulfillment of the role of the inspection bodies in the execution of public policy